PELATIHAN DETEKSI DINI NEUROPATI AKIBAT KEMOTERAPI - Hunaifi, Ilsa; Primayanti, Ika; Sapta Wardhani, Indah; Briliansy, Briliansy; Anggoro, Joko; Setyawati, Indri; Fesmia, Herodya Lajunee; Ismiana, Baiq Holisatul; Wiracakra, I Gusti Lanang Krisna; Gea, Endah Irnanda Ulfa; Jacob, Lusye Diana; Putri, Siti Noururrifqiyati Juna; Wardi, Bq. Prita Riantiani; Suryani, ⁠Dini; Andiyani, Dinda Zahra Putri (Jurnal Abdi Insani, 2025)
Cancer is currently a disease that is experiencing significant growth. This has resulted in the number of chemotherapy administrations reaching 9.8 million to 15 million people and increasing by 53%. One of the side effects that can be caused is peripheral nerve disorders called Chemotherapy-Induced Peripheral Neuropathy (CIPN). In connection with the increasing number of cancer patients undergoing chemotherapy and the severe impact on peripheral nerves due to chemotherapy, early detection is very important to prevent severe complications. This training aims to improve the knowledge and skills of medical personnel in the early detection of chemotherapy-induced neuropathy in order to improve the quality of life of patients and reduce complications and disabilities due to neuropathy. This training was carried out in collaboration with the West Nusa Tenggara Province General Hospital and was attended by 62 nurses. The series of training activities included delivering materials and direct practice to patients. Evaluation of participant knowledge was through a pre-test using the Kahoot application and a post-test using the Plataran Sehat application with a pre-test completion time of 5 minutes. The average pre-test score was 59.35, while the average post-test score was 79.35. The simulation sessions are conducted directly with patients using a neuropathy screening questionnaire, accompanied by a physician. The presentation of the material and the simulation sessions are highly beneficial in neuropathy screening, allowing early detection of neuropathy symptoms and prompt treatment.